Unlocking the potential of biocrust microorganisms in agriculture: cyanobacteria and heterotrophic bacteria with plant growth-promoting properties - Pagli, Carlotta; Maggioli, Lisa; Roncero-Ramos, Beatriz; Pajuelo, Eloisa; Muñoz-Rojas, Miriam; Braglia, Roberto; Canini, Antonella; Cantón, Yolanda (Frontiers in Plant Science, 2025)
IntroductionDrylands are subject to multiple overlapping stresses, including high temperatures, drought, and salinity, along with soils that are low in organic matter and nitrogen. Hence, both agricultural practices and natural regeneration in these areas are hindered by poor plant establishment and growth. The use of plant growth-promoting (PGP) microorganisms has recently emerged as a promising strategy to enhance plant performance under these harsh conditions.MethodsIn this context, the aim of this work was to isolate and screen the PGP properties of cyanobacteria and heterotrophic bacteria from biocrusts in arid soils, representing a highly unexplored niche of microorganisms with potential application in agriculture and ecological restoration. We determined key PGP traits, including phosphate and potassium solubilization, growth under nitrogen-free conditions, siderophore and auxin production, as well as protease, lipase, DNase, amylase, catalase, and cytochrome-C-oxidase activities.ResultsOur results showed that, among the cyanobacteria analyzed, Nostoc commune CANT2, isolated from the province of Almería (Spain), exhibited the highest number of PGP properties, followed by N. commune AB55 (southern Sardinia, Italy) and Trichocoleus cf. desertorum CAU7 (Almería). Both strains AB55 and CANT2 are characterized by their production of exopolysaccharides (EPS). Regarding the heterotrophic bacterial strains, those with the best PGP properties were identified as Peribacillus frigoritolerans and Bacillus atrophaeus by 16S rRNA gene sequencing. Seed biopriming experiments with the model plant Triticum aestivum showed that application of N. commune CANT2, either alone or in combination with P. frigoritolerans 1E, enhanced vigor indices by up to 58% compared to the control.DiscussionThese findings highlight the potential of combined microbial consortia with PGP activities as candidates for the development of biostimulants, offering a sustainable approach to improve plant growth and resilience in dryland agriculture.